Utopias, Dystopias and the Changing Lawscapes of Social Housing - Carr, Helen (feminists@law, 2013)
This paper provides an account of the design and development of the Spa Green Estate in North London. It describes the utopian aspirations for housing the working class of the radical 1930s Finsbury Council and the architect it employed, Berthold Lubetkin. It goes on to examine the political and popular discrediting of social housing from the 1970s and the consequent present day complexity of tenures and regulation on the estate. The account is placed in the context of the emergence of the claim that home ownership provides the appropriate solution for the housing of the working poor. It uses concepts of lawscape, utopia and scale to demonstrate how law is implicated in the dismantling of one utopian project and its replacement with another and the difficulties that law has in addressing the inevitable injustices that emerge from this process. Its feminism lies in its acknowledgement of social housing (despite its patriarchal origins) as an important point of access for women to the emancipation of the city and as a critical space for imagining ways to live other than those determined by the market.